1981
DOI: 10.1111/j.1600-0447.1981.tb00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines and monoamine oxidase activity in anxiety

Abstract: Levels of platelet monamine oxidase activity, state anxiety and trait anxiety were quantified twice in 20 drug-free subjects with generalized anxiety and an equal number of healthy drug-free controls at 4-week intervals. Fifteen subjects in each groups also had plasma epinephrine and norepinephrine measured. The index group received relaxation training during the interval between the two evaluation sessions. Post-relaxation training values for monoamine oxidase, epinephrine, norepinephrine and the anxiety leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

1984
1984
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 22 publications
1
16
1
Order By: Relevance
“…These stud¬ ies have confirmed that panic attacks are associated with various physiological changes, including that of increased heart rate and skin conductance. 21 25,1988) found no differences in plasma epinephrine, norepinephrine, or 3-methoxy-4-hydroxyphenyglycol levels between patients with GAD and nonanxious controls, even when they excluded patients with GAD with lower levels of anxiety. Also, another study that compared students who had high and low trait anxiety found no differences in plasma epinephrine or norepinephrine levels during rest or exercise.…”
mentioning
confidence: 93%
“…These stud¬ ies have confirmed that panic attacks are associated with various physiological changes, including that of increased heart rate and skin conductance. 21 25,1988) found no differences in plasma epinephrine, norepinephrine, or 3-methoxy-4-hydroxyphenyglycol levels between patients with GAD and nonanxious controls, even when they excluded patients with GAD with lower levels of anxiety. Also, another study that compared students who had high and low trait anxiety found no differences in plasma epinephrine or norepinephrine levels during rest or exercise.…”
mentioning
confidence: 93%
“…Consistent with this hypothesis, Wyatt et al [92] found a signifi cant correlation between total plasma cate cholamine concentration and severity of nurse-rated measures of anxiety, but not de pression, in depressed patients. CSF studies have demonstrated a positive correlation be tween measures of state anxiety and NE in depressed patients [57] and between anxiety and DBH in normals [5], Urinary MHPG has been reported to covary with changes in anx iety in affectively ill patients [80], In patients with both anxiety and depression, COMT levels are elevated in those patients who have mainly anxiety [66], Patients with anxiety disorders have been reported to have compa rable or higher levels of NE than controls [4,49,50]. Decreased MAO activity has been associated with the antianxiety effects of var ious treatments [16,40,50], while MAO activity is significantly increased in some pa tients with anxiety disorders [93], Since plasma MHPG reflects overall nor adrenergic activity, we investigated [90,91] the relationship between state anxiety and plasma MHPG in 12 healthy, normal volun teers exposed to a laboratory-controlled, anx iety-inducing situation.…”
Section: Indices Of Noradrenergic Functionmentioning
confidence: 99%
“…Another factor could have been the re sponse to stress. The plasma level of NE is indeed enhanced as a reaction to stress [Lake et al, 1976;Charney et al, 1984] or to anxiety [Mathew et al. 1981;Charney et al, 1984], Similar responses have been observed in the CNS [Redmond and Huang, 1979], responses which have been abolished by most of the anxiolytic drugs [Grant et al, 1980].…”
Section: Discussionmentioning
confidence: 72%